Open Educational Resources and Gateway Course Redesign: Reducing Student Costs While Sustaining Learning Quality - Jorge Castillo (Educational Innovation and Learning Transformation, 2026)
The rising cost of course materials creates a persistent barrier to equitable participation in higher education, particularly in high-enrollment gateway courses where textbook access shapes early academic momentum. Open Educational Resources (OER) are often promoted as a cost-saving solution, yet their strongest educational contribution may emerge when they are used to redesign gateway courses rather than merely replace commercial textbooks. This article examines how OER can reduce student costs while sustaining or improving learning quality through an evidence-informed gateway course redesign framework. Using a mixed-methods quasi-experimental model, the study illustrates an institutional redesign of five gateway courses enrolling 2,420 undergraduate students across biology, psychology, sociology, college algebra, and business foundations. The redesign combined no-cost OER adoption, faculty-led adaptation, assessment alignment, inclusive access design, and early-semester learning support. Published evidence indicates that OER generally produce learning outcomes comparable to commercial textbooks, with Clinton and Khan's meta-analysis reporting no meaningful difference in learning performance, g = 0.01, but lower withdrawal odds, OR = 0.71. Large-scale OER initiatives also show substantial affordability effects, including Achieving the Dream's $10.7 million in student savings across 38 community colleges and OpenStax's more than $3 billion in cumulative savings. The simulated results show reduced estimated course-material costs, lower DFW rates, stronger first-day access, and comparable or slightly improved learning outcomes. The article argues that OER should be understood as a lever for affordability, access, and pedagogical redesign.